2018
DOI: 10.1002/jcb.27966
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0076248 promotes oncogenesis of glioma by sponging miR‐181a to modulate SIRT1 expression

Abstract: Glioma is one of the most common primary malignancies of the central nervous system, which has aggressive clinical behavior and a poorer prognosis. MicroRNAs (miRs) are a class of small noncoding RNAs that function as mediators of gene expression, which can be sponged by circRNA provided with a closed circular structure. Dysregulations of circular RNAs (circRNAs) and miRs have been implicated in the development and progression of glioma. In the current study, we investigated the role of circular RNA hsa_circ_0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 55 publications
1
47
0
1
Order By: Relevance
“…Also, circRNA HIPK3 exhibited sponging multiple miRNAs, including tumor suppressor miR-124, miR-7, miR-4288, miR-654 [46,[49][50][51]. Previous studies indicated that circ_0034642 and circ_0076248 promoted glioma proliferation and invasion in the miR-1205/BATF3 axis and miR-181a/SIRT1 axis, respectively [52,53]. It seemed that these findings support the notion that the roles of circRNAs as miRNA sponge may be a general phenomenon.…”
Section: Functions Of Circular Rnassupporting
confidence: 58%
See 2 more Smart Citations
“…Also, circRNA HIPK3 exhibited sponging multiple miRNAs, including tumor suppressor miR-124, miR-7, miR-4288, miR-654 [46,[49][50][51]. Previous studies indicated that circ_0034642 and circ_0076248 promoted glioma proliferation and invasion in the miR-1205/BATF3 axis and miR-181a/SIRT1 axis, respectively [52,53]. It seemed that these findings support the notion that the roles of circRNAs as miRNA sponge may be a general phenomenon.…”
Section: Functions Of Circular Rnassupporting
confidence: 58%
“…Also, exosomal miR-1238 may confer chemoresistance in the tumor microenvironment, indicating that circulating miR-1238 acted as a promising therapeutic target for TMZ resistance in GBM [125]. Lei et al demonstrated that down-regulated hsa_circ_ 0076248 could remarkably promote the TMZ chemotherapy sensitivity via sponge miR-181a, which could suppress the expression of silent information regulator 1 (SIRT1) [52]. All these researches tend to make circRNAs become promising diagnostic/prognostic biomarkers and novel therapeutic targets.…”
Section: Circrnas Are Potential Novel Biomarkers For Diagnosis and Prmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] The aberrant expression of circRNA has been found in a wide variety of tumors, including GM. [10][11][12][13] For example, Lei et al 17 revealed that hsa_circ_0076248 could promote GM tumorigenesis through sponging miR-181a and regulate SIRT1 expression. Nevertheless, our knowledge of the roles of circRNAs might play in GM is still very limited.…”
Section: Circ-pitx1 Facilitates Cell Progression By Affecting Mir-5mentioning
confidence: 99%
“…They are distributed in neuronal tissues and exhibit key functions in brain diseases, including glioma [4,5]. For instance, Lei et al reported that circRNA hsa_circ_0076248 promotes proliferation and invasion of glioma by regulating miR-181 and silent information regulator 1 (SIRT1) [6]. Shi et al showed that hsa_circ_0014359 contributes to glioma progression by targeting miR-153/phosphatidylinositol 3 kinase (PI3K) signaling [7].…”
Section: Introductionmentioning
confidence: 99%